Weight Change and Risk of Atherosclerosis Measured by Carotid Intima–Media Thickness (cIMT) from a Prospective Cohort—Analysis of the First-Wave Follow-Up Data of the Canadian Longitudinal Study on Aging (CLSA) - Jian Liu; Newman Siu Kwan Sze; Miya Narushima; Deborah O’Leary (Journal of Cardiovascular Development and Disease, 2023)
To explore impact of weight change (WC) on risk of atherosclerosis measured by cIMT, 20,700 participants from the CLSA follow-up were included in analysis. WC was defined as the difference of weight measured at follow-up and baseline, then quartered into four groups (Q1–Q4). cIMT > 1.0 mm was defined as high risk for atherosclerosis. Adjusted odds ratio (OR (95% CI)) from logistic regression models were used to evaluate the association between WC and risk of atherosclerosis. At follow-up, participants had gained 0.118 kg weight, on average, and 16.4% of them were at high risk for atherosclerosis. The mean levels of cIMT were comparable between participants from Q1 to Q4. Compared to Q2 (reference), the ORs (95% CI) were 1.00 (0.86, 1.15), 1.19 (1.03,1.38), and 1.25 (1.08,1.45) for Q1, Q3, and Q4, respectively. A similar pattern was observed when analyses were conducted for ages < 65 vs. 65+ separately, but it was weaker for those aged 65+. Results from the jointed distribution analyses indicated that moderate weight loss might increase risk for atherosclerosis among participants with obese BMI at baseline, but not for those with cardiovascular event status at baseline. Weight gain, however, would increase risk for atherosclerosis regardless of cardiovascular event status, or overweight/obese BMI at baseline.